2019
DOI: 10.1111/gcb.14625
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts

Abstract: In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 75 publications
(133 reference statements)
3
95
0
Order By: Relevance
“…The large seasonal difference in aerosol loading implies a temperature-or irradiance-dependent biological influence. Furthermore, Modini et al (2009) observed nucleation events at Agnes Water in the southern GBR, in which corals were concluded to be the most likely source of precursor compounds. These events occurred in clean, easterly air masses originating in the MBL, when solar irradiance at the sea surface was high (∼ 1000 W m −2 ).…”
Section: Influence On Particle Formation and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The large seasonal difference in aerosol loading implies a temperature-or irradiance-dependent biological influence. Furthermore, Modini et al (2009) observed nucleation events at Agnes Water in the southern GBR, in which corals were concluded to be the most likely source of precursor compounds. These events occurred in clean, easterly air masses originating in the MBL, when solar irradiance at the sea surface was high (∼ 1000 W m −2 ).…”
Section: Influence On Particle Formation and Growthmentioning
confidence: 99%
“…This event occurred during a NNE wind, accumulating particles of marine origin from upwind coral reefs. The authors concluded that Aitken mode concentration was too low to have been derived from coagulation alone; thus new particles were largely derived from the condensation of low-volatility vapours such as DMS-derived H 2 SO 4 (Modini et al, 2009). Swan et al (2016) also measured high particle concentration over Heron Island in the southern GBR, which coincided with a peak in DMS emissions from the coral-reef flat during calm conditions after a low tide, again suggesting that the coral reef was a source of MBA precursor compounds.…”
Section: Influence On Particle Formation and Growthmentioning
confidence: 99%
“…These impacts are compounded by enhanced sedimentation from riverine discharge and dredging, which cause benthic smothering, increased turbidity and reduced light penetration, all of which adversely affect photosynthesising organisms including coral zooxanthellae (Erftemeijer et al, 2012). Sea-level rise and changes to large-scale oceanic circulation in response to global warming is exacerbating coastal erosion and declining water quality and has caused an increase in storm surges which further degrade coral reefs (Mellin et al, 2019). Measurements of dissolved DMS/P have been found to decline along a gradient of relatively pristine to human-impacted coral reefs in the central GBR (Jones et al, 2007).…”
Section: Water Quality and Eutrophicationmentioning
confidence: 99%
“…Sargassum biomass on inshore reefs of the GBR fluctuates seasonally and reaches a maximum during early summer and a minimum during mid-winter [36,39,40]. Macroalgae-dominated shallow inshore reefs of the GBR are also exposed to larger temperature fluctuations compared with off-shore reefs [41], with sea-surface temperature at inshore reefs frequently reaching 30°C during summer [42]. Hence, inshore regions of the GBR provide an ideal system to study the effects of macroalgae biomass, temperature, and nutrient fluctuations on the functional potential of coral reef microbiomes.…”
Section: Introductionmentioning
confidence: 99%